2009
DOI: 10.1165/rcmb.2008-0377oc
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Prevents Transforming Growth Factor-α–Induced Pulmonary Fibrosis

Abstract: Transforming growth factor (TGF)-alpha is a ligand for the epidermal growth factor receptor (EGFR). EGFR activation is associated with fibroproliferative processes in human lung disease and animal models of pulmonary fibrosis. Overexpression of TGF-alpha in transgenic mice causes progressive and severe pulmonary fibrosis; however, the intracellular signaling pathways downstream of EGFR mediating this response are unknown. Using a doxycycline-regulatable transgenic mouse model of lung-specific TGF-alpha express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 37 publications
3
80
2
Order By: Relevance
“…Our study also showed that RAPA treatment could not block the trend of body weight loss and may even worsen it. This result was inconsistent with some previous studies (Korfhagen et al, 2009;Madala et al, 2011). We speculate that this discrepancy may be caused mainly by the different animal models established: TGF-α-and bleomycin-induced pulmonary fibrosis might have less severe lung damage and a lower incidence of multiple organ dysfunction syndrome (MODS).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Our study also showed that RAPA treatment could not block the trend of body weight loss and may even worsen it. This result was inconsistent with some previous studies (Korfhagen et al, 2009;Madala et al, 2011). We speculate that this discrepancy may be caused mainly by the different animal models established: TGF-α-and bleomycin-induced pulmonary fibrosis might have less severe lung damage and a lower incidence of multiple organ dysfunction syndrome (MODS).…”
Section: Discussioncontrasting
confidence: 67%
“…In rat models of liver fibrosis, low-dose RAPA treatment can reduce collagen deposition (Neef et al, 2006). More recently, several studies have revealed that RAPA can prevent the progression of bleomycin-or transforming growth factor-α (TGF-α)-induced pulmonary fibrosis (Korfhagen et al, 2009;Madala et al, 2011). As a result, we hypothesized that RAPA treatment may be an effective therapy to ameliorate PQ-induced pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…7,25 However, mTOR is universally expressed regardless of cell types, so rapamycin was gradually used in anti-cancer and anti-fibrotic therapies. 11,26,27 We used N-and F-HLFs to demonstrate that rapamycin potently exerts direct profibrotic activities by promoting CCN2 expression in a Smad-independent and PI3K-dependent manner. In our sister paper, 28 we also showed rapamycin potentiates CCN2 expression in alveolar epithelial cells by PI3K pathway.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition to immunosuppressive effects, rapamycin also showed to be effective in preventing fibrogenesis in animal models. [11][12][13] However, the exact molecular mechanisms underlying the effects of rapamycin on preventing organ fibrosis remain poorly understood. Furthermore, the antifibrotic effect of rapamycin was seriously challenged by other studies, which showed that rapamycin had no significant improvements on fibrotic process.…”
mentioning
confidence: 99%
“…Artesunate treatment resulted in decreased collagen-IV protein in lung tissues and decreased collagen-IV mRNA in primary lung fibroblast cells, indicating that the anti-fibrotic effect of artesunate might be involve, at least partially, downregulation collagen-IV expression. MMP-2 and MMP-9 are well-known owing to their ability to degrade collagen-IV, and their increased activity leads to various pulmonary diseases including pulmonary fibrosis (Krämer et al, 2008;Bridle et al, 2009;Korfhagen et al, 2009). MMP-2 and MMP-9 play an important role in the inefficient remodeling of damaged lung tissue (Checa et al, 2008;Yamashita et al, 2011;Song et al, 2013).…”
Section: Discussionmentioning
confidence: 99%